Revised International Prognostic Index and genetic alterations are associated with early failure to R‐CHOP in patients with diffuse large B‐cell lymphoma. (10th October 2021) - Dlouhy, Ivan; Karube, Kennosuke; Enjuanes, Anna; Salaverria, Itziar; Nadeu, Ferran; Ramis‐Zaldivar, Juan Enric; Valero, Juan G.; Rivas‐Delgado, Alfredo; Magnano, Laura; Martin‐García, David; Pérez‐Galán, Patricia; Clot, Guillem; et al.
Summary: Relapsed or refractory diffuse large B‐cell lymphoma (DLBCL) cases have a poor outcome. Here we analysed clinico‐biological features in 373 DLBCL patients homogeneously treated with rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone (R‐CHOP), in order to identify variables associated with early failure to treatment (EF), defined as primary refractoriness or relapse within 12 months from diagnosis. In addition to clinical features, mutational status of 106 genes was studied by targeted next‐generation sequencing in 111 cases, copy number alterations in 87, and gene expression profile (GEP) in 39. Ninety‐seven cases (26%) were identified as EF and showed significantly shorter overall survival (OS). Patients with B symptoms, advanced stage, high levels of serum lactate dehydrogenase (LDH) or β2‐microglobulin, low lymphocyte/monocyte ratio and higher Revised International Prognostic Index (R‐IPI) scores, as well as those with BCL2 rearrangements more frequently showed EF, with R‐IPI being the most important in logistic regression. Mutations in NOTCH2, gains in 5p15·33 ( TERT ), 12q13 ( CDK2 ), 12q14·1 ( CDK4 ) and 12q15 ( MDM2 ) showed predictive importance for EF independently from R‐IPI. GEP studies showed that EF cases were significantly enriched in sets related to cell cycle regulation and inflammatory response, while cases in response showed over‐representation of gene sets related to extra‐cellular matrix and tumour microenvironment.